Ferdinand and Elefant tank destroyer - Anderson, Thomas (Osprey Publishing, 2015)
A study that explores the technical development and combat deployment of the Ferdinand, from its' origins in the Porsche Tiger Tank through its deployment under the designation 'Ferdinand' in the Citadel offensive, to its modification and redesignation as the 'Elefant' and final use in the desperate Battle of Berlin.